Pengaruh Keteladanan Guru Pendidikan Agama Kristen terhadap Moral Siswa Kelas VIII SMP Negeri 2 Tarutung Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024 - Sahnila Putri Berutu; Dorlan Naibaho; Grecetinovitria M. Butar-butar; Boho P. Pardede; Maryska Debora Silalahi (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
The purpose of this study was to determine the positive and significant influence of Christian Religious Education Teacher Exemplar on the Morals of Class VIII Students of SMP Negeri 2 Tarutung, North Tapanuli Regency, in the 2023/2024 Academic Year. The method used in this study is a quantitative research method with descriptive statistics. The population was all class VIII students of SMP Negeri 2 Tarutung, totaling 175 people, and a sample of 35 people was determined using random sampling techniques. Data were collected using a positive closed questionnaire of 42 items. The results of the data analysis show that there is a positive and significant influence of the Exemplary Christian Religious Education Teacher on the Morals of Class VIII Students of SMP Negeri 2 Tarutung, North Tapanuli Regency in the 2023/2024 Academic Year: 1) Analysis requirements test: a) positive relationship test obtained rxy value = 0.676> rtable ( = 0.05, n = 35) = 0.334 thus it is known that there is a positive relationship between variable X and variable Y. b) Significant relationship test obtained tcount value = 5.266> t table ( = 0.05, dk = n-2 = 33) = 2.042 thus there is a significant relationship between variable X and variable Y. 2) Influence test: a) Regression equation test, obtained regression equation Ŷ = 35.12 + 0.24. b) Regression determination coefficient test (r2) = 45.7%. 3) Hypothesis testing using the F test obtained Fcount > Ftable, namely 27.73 > 1.62. Thus, Ha is accepted and H0 is rejected. Thus, it can be seen that the research hypothesis proposed by the author is accepted, namely that there is a positive and significant influence of the Exemplary Behavior of Christian Religious Education Teachers on the Morals of Class VIII Students of SMP Negeri 2 Tarutung, North Tapanuli Regency, 2023/2024 Academic Year.